Comparison of the patterns of antibody recall responses to HIV-1 gp120 and hepatitis B surface antigen in immunized mice. Issue 50 (7th December 2016) - Yu, Hao-Tong; Wang, Jia-Ye; Tian, Dan; Wang, Ming-Xia; Li, Yan; Yuan, Li; Chen, Wen-Jiang; Li, Di; Zhuang, Min; Ling, Hong
Abstract: To date, we still lack an ideal strategy for designing envelope glycoprotein (Env) vaccines to elicit potent protective antibodies against HIV-1 infection. Since the human hepatitis B virus surface antigen (HBsAg) is representative of effective vaccines that can induce ideal humoral immune responses, knowledge of how it elicits antibody responses and T helper cells would be an useful reference for HIV vaccine development. We compared the characteristics of the HIV-1 Env gp120 trimer and HBsAg in antibody elicitation and induction of T follicular helper (Tfh) and memory B cells in immunized Balb/c mice. Using the strategy of protein prime-protein boost, we found that HIV-1 gp120 induced slower recall antibody responses but redundant non-specific IgG responses at early time after boosting compared to HBsAg. The higher frequency of PD-1 hi CD4 + T cells and Tfh cells that appeared at the early time point after gp120 boosting is likely to limit the development of memory B cells, memory T cells, and specific antibody recall responses. These findings regarding the different features of HIV envelope and HBsAg in T helper cell responses may provide a direction to improve HIV envelope immunogenicity.